A Study on Udder Health Management Practices, Reproductive Disorders and Subclinical Mastitis in Buffalo Herds in Coastal Region of Bangladesh - Dibyendu Biswas; SM Hanif; Eaftekhar Ahmed Rana; AKM Mostafa Anower (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Mastitis is an economically important disease of intensive buffalo dairy farming worldwide. Detection of subclinical mastitis (SCM) is important for its management and control. The purpose of this study was to estimate the prevalence of reproductive disorders, SCM and udder health management practices in the buffalo dairy farms of Bhola District, Bangladesh. Data on animal demographics, reproduction status, daily milk yield and status of California Mastitis Test (CMT) result were recorded. A total of 402 buffaloes were observed in two farms at Bhola district and among them 70 milking buffaloes were randomly selected for CMT. The overall prevalence of SCM in buffalo was 20.0%. Young age group of buffaloes was more susceptible for SCM and it was not significant difference. Parity and stage of lactation have no any effect on SCM. However, abortion case was more susceptible to SCM than other diseases but not any significant difference. During milking the milkers never use any antiseptic solution for washing the udder and never use any feed supply during milking. Among the isolated organisms Staphylococcus spp. and E. coli were found more frequent in the study area and gentamicin and ciprofloxaclin were most sensitive to the isolated organisms. From this study it was concluded that buffalo’s udder was very resistance to SCM infection and udder management practice was very poor. Common antibiotics were resistance to isolated organisms from SCM case. Gentamicin and ciprofloxacin were found more susceptible against all four isolated organisms.